Dietary supplements : safety, efficacy and quality - Berginc, Katja; Kreft, Samo 1972- (Woodhead Publishing, 2015)
Dietary supplements made from foods, herbs and their constituents are a rapidly growing market sector. Consumers often view food supplements as 'natural' and therefore safe; however, supplements are regulated as foods rather than as pharmaceuticals and so are not as closely monitored as may be necessary. With the commercial market in these products growing, this book provides essential research into their safety, efficacy and potential risk of interaction with pharmaceuticals. Following an introductory chapter, part one covers the chemical composition, manufacture and regulation of dietary supplements. Part two looks at the effectiveness of different types of dietary supplement and methods of evaluation. Finally, part three focuses on supplement safety.
Keywords: potravní doplňky; bezpečnost potravin; interakce léčiv; dietary supplements; food safety; drug interactions; elektronické knihy; electronic books